The state of coursework on horses in human services at universities and colleges in the United States: a scoping review - Connolly, Katherine; Ekholm Fry, Nina (Frontiers in Veterinary Science, 2023)
An increasing number of universities and colleges in the United States are offering coursework on adaptive/therapeutic riding and the incorporation of horses in human service areas such as psychotherapy, education, occupational therapy, physical therapy, and speech-language pathology. The first study to identify coursework in these areas was published in 2018. In order to track development over time, we conducted a replication study to determine the prevalence of coursework on horses in human services at higher education institutions. Information gathered for the 2021-2022 academic year included the institution name, geographic location, number of courses and their focus, academic department offering the course, and level of study. We identified 122 courses provided by 48 higher education institutions in 29 states in the following areas: adaptive/therapeutic riding (N = 82, 67.2%), mental health (N = 19, 15.6%), education/learning (N= 2, 1.6%), and equine movement in physical therapy, occupational therapy, and speech-language pathology (hippotherapy) (N = 1, 0.8%). Survey or overview courses (N = 18, 14.8%) were also identified. These courses were offered both at the undergraduate (N = 114, 93.4%) and the graduate level (N = 8, 6.6%) by a total of 48 departments that either focused on animals, such as equine science, animal science, and agriculture (N = 27, 54%) or focused on humans, such as health science or liberal arts (N = 23, 46%). The results inform a discussion on changes over time as well as current challenges and opportunities for academic programs offering coursework about horses in human services.